Regeneration of Deteriorated Internal Combustion Engine Components used in Thermal Power Plants - William Quitiaquez; Hugo Meneses; Patricio Quitiaquez; Isaac Simbaña (Revista Técnica Energía)
The generation of electric power through internal combustion engines plays an important role in the world economy. Exhaust cases and valves are critical engine components and are subjected to high pressures and temperatures. The additive remanufacturing technology of mechanical components that have reached the end of their useful life due to wear, through the L-DED laser directed energy deposition method, proves to be an effective method to obtain spare parts with similar or even superior characteristics to a new part, extending the product life cycle in the circular economy. The process consists of obtaining 3D models through reverse engineering, additive remanufacturing by L-DED and final machining. It was determined through the study that this methodology can be successfully applied to the exhaust boxes and valves of internal combustion engines for electric generation. The results obtained have shown that this remanufacturing method is an effective solution for the recovery of exhaust boxes and valves that have completed their useful life and can be applied to other engine elements, reducing the cost of the spare part compared to a new one and bringing with it important environmental benefits. In reference to the remanufacturing time, it has been determined that the application of the L-DED process in the exhaust boxes and valves is 3943 and 3677 s respectively. In addition to this time, the time used in the initial preparation and final machining must be added; however, the time is substantially less than the manufacturing of a new spare part, which brings with it an increase in the availability of these spare parts to perform scheduled maintenance in the engines for power generation, contributing to improve the efficiency of the national electric system.